Binder resin composition for toner

By using composite resins of polyester resin, vinyl resin and polyphenol vinyl ester in electro-optical image development agents, the problem of insufficient image density and thin line resilience in the prior art is solved, and higher image quality and speed are achieved.

JP7658674B2Active Publication Date: 2025-04-08KAO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021158223
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-28
Publication Date
2025-04-08
Estimated Expiration
2041-09-28

AI Technical Summary

Technical Problem

Existing electro-optical image developers have shortcomings in improving image quality and speed, especially in terms of image density and thin line restoration.

Method used

A composite resin comprising a polyester resin segment, a vinyl resin segment and polyphenol vinyl ester is used as a binding agent for the electro-optical image development agent. The aggregate formed by the composite resin through copolymerization reaction has high molecular fluidity and polarization, and improves the charge transport capability and thermal performance of the electro-optical image developer.

Benefits of technology

The image density and thin line recovery are significantly improved, the positive charge characteristics and dielectric constant of the electro-optical image developer are enhanced, thereby improving image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658674000001
    Figure 0007658674000001
  • Figure 0007658674000002
    Figure 0007658674000002
  • Figure 0007658674000003
    Figure 0007658674000003
Patent Text Reader

Abstract

To provide a binder resin composition for a toner capable of improving the image quality of printed matter such as the image density and the fine line reproducibility by using an electrophotographic toner.SOLUTION: A binder resin composition for a toner contains a condensate (AP) composed of: a composite resin (A) containing a polyester resin segment which is polycondensate of an alcohol component and a carboxylic acid component, and a vinyl resin segment which is an addition polymerization product of a raw material monomer containing a styrene compound; and polyalkyleneimine (P).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder resin composition for toners used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like, and to an electrophotographic toner containing the binder resin composition for toners. [Background technology]

[0002] In the field of electrophotography, with the development of electrophotographic systems, there is a demand for the development of toners that can handle higher image quality and higher speeds. Patent Document 1 describes a toner for developing electrostatic images, which includes a colorant, a resin composition obtained by condensing an amorphous polyester resin having an acid group with an amine compound, and one or more ester compositions selected from an ester composition (CI) containing a condensate of a carboxylic acid component containing 20 mol% or more of an aliphatic monocarboxylic acid compound and an alcohol component containing 90 mol% or more of a divalent or higher aliphatic alcohol, and an ester composition (CII) containing a condensate of an alcohol component containing 20 mol% or more of an aliphatic monoalcohol and a carboxylic acid component containing 90 mol% or more of a divalent or higher aliphatic carboxylic acid compound. The toner is described as having excellent image density and gloss. Patent Document 2 describes a dry toner using a polyester in which at least a part of COOH is replaced by a functional group containing N, such as amine, ammonium, betaine, pyridinium salt, or azine. It is described that the toner is a positively charged toner that develops a negative electrostatic latent image in a positive direction, and exhibits stable developability against environmental changes and over time. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-47403 [Patent Document 2] Japanese Patent Application Publication No. 14644 / 1983 Summary of the Invention [Problem to be solved by the invention]

[0004] However, there is a demand for further improvement in image quality in response to higher image quality and higher speeds. The present invention relates to a binder resin composition for a toner, which can improve the image quality of printed matter, such as image density and fine line reproducibility, by using the composition in an electrophotographic toner. [Means for solving the problem]

[0005] The present inventors have found that the above problems can be solved by a binder resin composition for toner, which contains a condensate of a composite resin including a polyester resin segment and a vinyl resin segment, and a polyalkyleneimine.

[0006] That is, the present invention relates to the following [1] and [2]. [1] A binder resin composition for toners, comprising a condensate (AP) of a composite resin (A) including a polyester resin segment which is a polycondensate of an alcohol component and a carboxylic acid component, and a vinyl resin segment which is an addition polymerization product of a raw material monomer including a styrene compound, and a polyalkyleneimine (P). [2] An electrophotographic toner comprising the binder resin composition for toners according to [1]. Effect of the Invention

[0007] According to the present invention, it is possible to provide a binder resin composition for a toner, which can improve the image quality of a printed matter, such as image density and fine line reproducibility, by using the composition in an electrophotographic toner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Binder resin composition for toner] The binder resin composition for toner of the present invention contains a condensate (AP) of a composite resin (A) including a polyester resin segment which is a polycondensate of an alcohol component and a carboxylic acid component, and a vinyl resin segment which is an addition polymerization product of a raw material monomer including a styrene compound, and a polyalkyleneimine (P). By using the binder resin composition for toners having the above-mentioned constitution in toners for electrophotography, it is possible to obtain a binder resin composition for toners that can improve the image quality of printed matter, such as image density and fine line reproducibility. The reason for this is not clear, but is thought to be as follows.

[0009] The toner binder resin composition of the present invention contains a condensate (AP) of a composite resin (A) containing a polyester resin segment and a vinyl resin segment which is an addition polymer of a raw material monomer containing a styrene-based compound, and a polyalkyleneimine (P). The composite resin (A) has a polyester resin segment which is relatively easy to move molecularly, and a vinyl resin segment which is an addition polymer of a raw material monomer containing a styrene-based compound with a high aromatic ring concentration which is relatively difficult to move molecularly, so that the polyester resin segment is easily polarized and the vinyl resin segment is not easily polarized. In addition, by introducing a polyalkyleneimine (P) into the composite resin (A), it is possible to impart positive charging to the nitrogen atom of the obtained condensate (AP), and the thermal properties such as the glass transition temperature are reduced, thereby further improving the molecular mobility of the polyester resin segment. Therefore, in the condensate (AP) contained in the binder resin composition for toner of the present invention, a segment that is easily polarized and a segment that is not easily polarized coexist in the same molecule of the composite resin (A), so that positive and negative pairs are less likely to be generated in the electric field in the composite resin (A), and the polarization becomes larger, so that the improvement in the dielectric constant and the increase in the positive chargeability due to the introduction of the polyalkyleneimine (P) are strongly exhibited. As a result, it is considered that the toner containing the binder resin composition for toner of the present invention has an improved dielectric constant and is more likely to maintain positive chargeability, thereby improving the image quality of printed matter, such as image density and fine line reproducibility.

[0010] The definitions of various terms used in this specification are given below. Whether a resin is crystalline or amorphous is determined by the crystallinity index. The crystallinity index is defined as the ratio of the softening point of the resin to the endothermic maximum peak temperature (softening point (°C) / endothermic maximum peak temperature (°C)) in the measurement method described in the Examples below. A crystalline resin is a resin with a crystallinity index of 0.6 or more and 1.4 or less. An amorphous resin is a resin in which no endothermic peak is observed, or in which the crystallinity index is greater than 1.4 or less than 0.6 when an endothermic peak is observed. The crystallinity index can be appropriately adjusted depending on the type and ratio of raw material monomers, as well as production conditions such as reaction temperature, reaction time, and cooling rate. The endothermic maximum peak temperature refers to the temperature of the endothermic peak with the largest peak area among the endothermic peaks observed under the conditions of the measurement method described in the Examples. In the specification, the carboxylic acid component of the polyester resin includes not only the exemplified compounds, but also anhydrides that decompose during the reaction to produce an acid, and alkyl esters of each carboxylic acid (alkyl groups having 1 to 3 carbon atoms). In the present specification, the term "binder resin composition" refers to a resin component contained in a toner that contains a condensate (AP) of a composite resin (A) and a polyalkyleneimine (P).

[0011] <Condensation product (AP)> The condensate (AP) is a condensate (AP) of the composite resin (A) and the polyalkyleneimine (P). The condensate (AP) is formed by a condensation reaction between the composite resin (A) and the polyalkyleneimine (P). The condensate (AP) may contain, for example, a reaction product between the composite resin (A) and the polyalkyleneimine (P), a by-product derived from the polyalkyleneimine (P), an unreacted composite resin (A), an unreacted polyalkyleneimine (P), and the like, to an extent that does not substantially impair its properties. The condensate (AP) is preferably an amorphous resin.

[0012] (Composite resin (A)) The composite resin (A) contains a polyester resin segment which is a polycondensation product of an alcohol component and a carboxylic acid component, and a vinyl resin segment which is an addition polymerization product of a raw material monomer including a styrene compound. The composite resin (A) is preferably amorphous.

[0013] [Polyester resin segment] Examples of the alcohol component of the polyester resin segment include alkylene oxide adducts of aromatic diols, linear or branched aliphatic diols, alicyclic diols, and trivalent or higher polyhydric alcohols. Among these, alkylene oxide adducts of aromatic diols are preferred from the viewpoint of improving the molecular mobility of the polyester resin segment in the composite resin (A) and improving image density and fine line reproducibility.

[0014] The alkylene oxide adduct of an aromatic diol is preferably an alkylene oxide adduct of bisphenol A, more preferably an alkylene oxide adduct of formula (I):

[0015] [ka] (In the formula, OR 1 and R 2 O is an oxyalkylene group, and R 1 and R 2 are each independently an ethylene group or a propylene group, x and y are each an average number of moles of alkylene oxide added and are each a positive number, and the sum of x and y is 1 or more and 16 or less.

[0016] Examples of the alkylene oxide adduct of bisphenol A include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These may be used alone or in combination of two or more. From the viewpoint of improving the molecular mobility of the polyester resin segment in the composite resin (A) and improving the image density and fine line reproducibility, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and is 100 mol % or less, even more preferably 100 mol %.

[0017] Examples of linear or branched aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol. Examples of alicyclic diols include hydrogenated bisphenol A [2,2-bis(4-hydroxycyclohexyl)propane] and alkylene oxide adducts of hydrogenated bisphenol A having 2 to 4 carbon atoms (average number of moles added: 2 to 12). Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol. These alcohol components may be used alone or in combination of two or more.

[0018] Examples of the carboxylic acid component include dicarboxylic acids and polycarboxylic acids having 3 or more valences. Hereinafter, dicarboxylic acids and / or polycarboxylic acids having 3 or more valences are also simply referred to as "polycarboxylic acids". Examples of the dicarboxylic acid include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred from the viewpoint of improving the molecular mobility of the polyester resin segment in the composite resin (A) and improving the image density and fine line reproducibility. Examples of aromatic dicarboxylic acids include phthalic acid, isophthalic acid, and terephthalic acid. Among these, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. From the viewpoint of improving the molecular mobility of the polyester resin segment in the composite resin (A) and improving the image density and fine line reproducibility, the amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and is preferably 95 mol % or less, more preferably 93 mol % or less, even more preferably 90 mol % or less.

[0019] The linear or branched aliphatic dicarboxylic acid preferably has 2 or more, more preferably 3 or more, and preferably has 30 or less, more preferably 20 or less. Examples of linear or branched aliphatic dicarboxylic acids include oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, sebacic acid, dodecanedioic acid, azelaic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms. Examples of succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among these, fumaric acid, sebacic acid, and succinic acid substituted with an aliphatic hydrocarbon group having 1 to 20 carbon atoms are preferred, and fumaric acid is more preferred. The amount of linear or branched aliphatic dicarboxylic acid in the carboxylic acid component is preferably 1 mol % or more, more preferably 3 mol % or more, even more preferably 10 mol % or more, and is preferably 30 mol % or less, more preferably 25 mol % or less, even more preferably 20 mol % or less.

[0020] The trivalent or higher polyvalent carboxylic acid is preferably a trivalent carboxylic acid, for example, trimellitic acid, and is preferably trimellitic acid or its anhydride. When a trivalent or higher polycarboxylic acid is contained, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 3 mol% or more, more preferably 5 mol% or more, even more preferably 8 mol% or more, and is preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 20 mol% or less. These carboxylic acid components may be used alone or in combination of two or more.

[0021] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0022] [Vinyl resin segment] The vinyl resin segment is an addition polymer of raw material monomers including a styrene compound. Examples of the styrene-based compound include unsubstituted or substituted styrene. Examples of the substituent substituted on styrene include an alkyl group having 1 to 5 carbon atoms, a halogen atom, an alkoxy group having 1 to 5 carbon atoms, a sulfonic acid group, or a salt thereof. Examples of styrene-based compounds include styrene, methylstyrene, α-methylstyrene, β-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, methoxystyrene, styrenesulfonic acid, and salts thereof. Among these, styrene is preferred. The content of the styrene-based compound in the raw material monomers of the vinyl-based resin segment is, from the viewpoint of suppressing polarization of the vinyl resin segment in the composite resin (A) and improving image density and fine line reproducibility, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and is 100% by mass or less, even more preferably 100% by mass.

[0023] When the raw material monomer constituting the vinyl resin segment contains a raw material monomer other than a styrene compound, the raw material monomer may be, for example, (meth)acrylic acid esters such as alkyl (meth)acrylate, benzyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; olefins such as ethylene, propylene, and butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, (meth)acrylic acid esters are preferred, and alkyl (meth)acrylates are more preferred. The number of carbon atoms in the alkyl group in the alkyl (meth)acrylate is preferably 1 or more, more preferably 4 or more, even more preferably 6 or more, and is preferably 24 or less, more preferably 22 or less, even more preferably 20 or less. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, (iso or tertiary)butyl (meth)acrylate, (iso)amyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, (iso)dodecyl (meth)acrylate, (iso)palmityl (meth)acrylate, (iso)stearyl (meth)acrylate, and (iso)behenyl (meth)acrylate. Of these, 2-ethylhexyl (meth)acrylate or stearyl (meth)acrylate is preferred, 2-ethylhexyl acrylate and stearyl (meth)acrylate are more preferred, and 2-ethylhexyl acrylate is even more preferred. In addition, "(iso or tertiary)" and "(iso)" refer to both the presence and absence of these prefixes, and the absence of these prefixes indicates normal. In addition, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid.

[0024] When the raw material monomer constituting the vinyl resin segment contains a (meth)acrylic acid ester, the content of the (meth)acrylic acid ester in the raw material monomer for the vinyl resin segment is preferably 1 mass % or more, more preferably 3 mass % or more, even more preferably 5 mass % or more, and preferably 30 mass % or less, more preferably 25 mass % or less, even more preferably 20 mass % or less. The total amount of the styrene compound and the (meth)acrylic acid ester in the raw material monomers of the vinyl resin segment is preferably 80 mass % or more, more preferably 90 mass % or more, even more preferably 95 mass % or more, and still more preferably 100 mass %.

[0025] [Constituent units derived from bireactive monomers] The composite resin (A) preferably has a structural unit derived from a bireactive monomer bonded to a polyester resin segment and a vinyl resin segment via a covalent bond. The term "structural unit derived from a bireactive monomer" refers to a unit formed by reaction of a functional group and an addition polymerizable group of a bireactive monomer. An example of the addition polymerizable group is a carbon-carbon unsaturated bond (ethylenically unsaturated bond). Examples of the bireactive monomer include addition polymerizable monomers having at least one functional group selected from a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group in the molecule. Among these, from the viewpoint of reactivity, addition polymerizable monomers having at least one functional group selected from a hydroxyl group and a carboxyl group are preferred, and addition polymerizable monomers having a carboxyl group are more preferred. Examples of the addition polymerizable monomer having a carboxy group include acrylic acid, methacrylic acid, fumaric acid, and maleic acid. Among these, from the viewpoint of reactivity in both the polycondensation reaction and the addition polymerization reaction, acrylic acid and methacrylic acid are preferred, and acrylic acid is more preferred. When the bireactive monomer is an addition polymerizable monomer having a carboxy group, the amount of the constitutional units derived from the bireactive monomer is preferably 0.5 mol parts or more, more preferably 1 mol parts or more, and even more preferably 2 mol parts or more, relative to 100 mol parts of the alcohol component of the polyester resin segment of the composite resin (A), and is preferably 15 mol parts or less, more preferably 10 mol parts or less, and even more preferably 7 mol parts or less.

[0026] The content of the vinyl resin segment in the composite resin (A) is preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 8% by mass or more, even more preferably 13% by mass or more, and even more preferably 17% by mass or more, and is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 23% by mass or less, based on the total amount of the polyester resin segment and the vinyl resin segment. The content of the polyester resin segment in the composite resin (A) is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 77% by mass or more, and is preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 92% by mass or less, even more preferably 87% by mass or less, and even more preferably 83% by mass or more, based on the total amount of the polyester resin segment and the vinyl resin segment. The bireactive monomer-derived structural unit is included in the polyester resin segment for calculation.

[0027] The content of the structural units derived from the bireactive monomer in the composite resin (A) is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, relative to the total amount of the polyester resin segment and the vinyl resin segment, and is preferably 10 mass% or less, more preferably 7 mass% or less, and even more preferably 4 mass% or less.

[0028] The above amount is calculated based on the ratio of the amounts of the polyester resin segment, the raw material monomer for the vinyl resin segment, the bireactive monomer, and the radical polymerization initiator, and the mass of the polyester resin segment, etc. is based on the mass excluding the mass of water generated by polycondensation. When a radical polymerization initiator is used, the mass of the radical polymerization initiator is calculated by including it in the vinyl resin segment.

[0029] [Method for producing composite resin (A)] The composite resin (A) may be produced, for example, by a method including a step A of polycondensing an alcohol component and a carboxylic acid component, and a step B of addition polymerizing raw material monomers for a vinyl resin segment and a bireactive monomer. Step B may be carried out after step A, step B may be carried out after step A, or step A and step B may be carried out simultaneously. A method is preferred in which a part of the carboxylic acid component is subjected to a polycondensation reaction in step A, and then step B is carried out, and thereafter the remainder of the carboxylic acid component is added to the polymerization system to further proceed with the polycondensation reaction in step A and the polycondensation reaction with the carboxy group of the bireactive monomer or the constituent moiety derived from the bireactive monomer.

[0030] In step A, if necessary, polycondensation may be performed using an esterification catalyst such as tin(II) di(2-ethylhexanoate), dibutyltin oxide, titanium diisopropoxybis(triethanolaminate) in an amount of 0.001 part by mass or more and 5 parts by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component, and an esterification promoter such as gallic acid (same as 3,4,5-trihydroxybenzoic acid) in an amount of 0.0001 part by mass or more and 0.5 part by mass or less per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. When a monomer having an unsaturated bond such as fumaric acid is used in polycondensation, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.0001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol. The temperature of the polycondensation reaction is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 140° C. or higher, and is preferably 250° C. or lower, and more preferably 240° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.

[0031] Examples of the radical polymerization initiator for the addition polymerization in step B include peroxides such as dibutyl peroxide, persulfates such as sodium persulfate, and azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile). The amount of the radical polymerization initiator used is preferably 1 part by mass or more and 20 parts by mass or less based on 100 parts by mass of the raw material monomer of the vinyl resin segment. The temperature of the addition polymerization is preferably 110° C. or higher, more preferably 130° C. or higher, and preferably 230° C. or lower, more preferably 220° C. or lower, and further preferably 210° C. or lower.

[0032] (Polyalkyleneimine (P))

[0033] The polyalkyleneimine (P) is preferably a polyalkyleneimine having an alkylene group with 2 or more and 6 or less carbon atoms, more preferably a polyalkyleneimine having an alkylene group with 2 or more and 4 or less carbon atoms, even more preferably a polyethyleneimine or polypropyleneimine, and even more preferably a polyethyleneimine. The polymer structure of the polyalkyleneimine (P) may be a linear or branched structure, among which a branched structure is preferred from the viewpoints of improving the dielectric constant of the condensate (AP), increasing the positive chargeability, and improving the image density and fine line reproducibility. When the polyalkyleneimine (P) has a branched structure, it may have a tertiary amino group and a primary amino group in addition to a secondary amino group (imino group) in the structure. When the polyalkyleneimine (P) has a branched structure, the total proportion of primary amino groups and secondary amino groups in the amino groups of the alkyleneimine is preferably 50% or more, more preferably 60% or more, even more preferably 65% ​​or more, and preferably 100% or less. The total ratio of the primary amino group and the secondary amino group is 13 It is determined by C-NMR.

[0034] From the viewpoint of reactivity with the composite resin (A), the number average molecular weight of the polyalkyleneimine (P) is preferably 150 or more, more preferably 300 or more, and even more preferably 500 or more, and is preferably 3,000 or less, more preferably 2,000 or less, and even more preferably 1,000 or less. The molecular weight value is determined by the method described in the Examples.

[0035] The content of the constitutional unit derived from the polyalkyleneimine (P) in the condensate (AP) is, from the viewpoints of improving the dielectric constant of the condensate (AP), increasing the positive chargeability, and improving the image density and fine-line reproducibility, preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less, even more preferably 3% by mass or less.

[0036] [Method for producing condensation product (AP)] The condensation of the composite resin (A) with the polyalkyleneimine (P) may be performed by directly condensing the acid group of the composite resin (A) with the secondary amino group and / or primary amino group of the polyalkyleneimine (P), or by condensing the hydroxyl group of the composite resin (A) with the secondary amino group and / or primary amino group of the polyalkyleneimine (P) via a dicarboxylic acid and / or a polyvalent carboxylic acid having three or more valences. As the polyvalent carboxylic acid, the carboxylic acids listed as the carboxylic acid component of the polyester resin segment can be used, and preferably, a linear or branched aliphatic dicarboxylic acid, more preferably, one or more selected from succinic acid, fumaric acid, and sebacic acid, and even more preferably, fumaric acid.

[0037] The condensation of the acid group of the composite resin (A) with the polyalkyleneimine (P) can be carried out by heating them and removing water produced by the dehydration reaction from the system under reduced pressure or the like. When a monomer having an unsaturated bond such as fumaric acid is used, a radical polymerization inhibitor may be used, if necessary, in an amount of preferably 0.0001 to 0.5 parts by mass per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. An example of the radical polymerization inhibitor is 4-tert-butylcatechol. The temperature of the condensation reaction is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 140° C. or higher, and is preferably 250° C. or lower, more preferably 230° C. or lower, and even more preferably 210° C. or lower. The condensation may be carried out in an inert gas atmosphere.

[0038] [Physical properties of condensation product (AP)] The dielectric constant of the condensate (AP) is preferably 1.5×10 -13 / cm or more, more preferably 1.8×10 -13 / cm or more, more preferably 2.0×10 -13 / cm or more, more preferably 2.2×10 -13 / cm or more, more preferably 2.4×10 -13 / cm or more, more preferably 2.5×10 -13 / cm or more, more preferably 2.7×10 -13 / cm or more, and preferably 3.5×10 -13 / cm or less, more preferably 3.2×10 -13 / cm or less, more preferably 3.0×10 -13 / cm or less.

[0039] The glass transition temperature of the condensate (AP) is preferably 30° C. or higher, more preferably 35° C. or higher, and even more preferably 40° C. or higher, and from the viewpoint of further improving the low-temperature fixability, is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 60° C. or lower. The softening point of the condensate (AP) is preferably 70° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher, and from the viewpoint of further improving the low-temperature fixability, it is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 125° C. or lower.

[0040] The acid value of the condensate (AP) is preferably 2 mgKOH / g or more, more preferably 3 mgKOH / g or more, even more preferably 5 mgKOH / g or more, and preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, even more preferably 10 mgKOH / g or less. The hydroxyl value of the condensate (AP) is preferably 20 mgKOH / g or more, more preferably 30 mgKOH / g or more, even more preferably 35 mgKOH / g or more, and preferably 60 mgKOH / g or less, more preferably 55 mgKOH / g or less, even more preferably 50 mgKOH / g or less. The amine value of the condensate (AP) is preferably 5 mgKOH / g or more, more preferably 8 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and is preferably 80 mgKOH / g or less, more preferably 50 mgKOH / g or less, even more preferably 20 mgKOH / g or less.

[0041] The dielectric constant, glass transition temperature, softening point, acid value, hydroxyl value, and amine value of the condensate (AP) can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values ​​can be determined by the methods described in the Examples. When two or more kinds of condensates (AP) are used in combination, the dielectric constant, glass transition temperature, softening point, acid value, hydroxyl value, and amine value obtained as a mixture thereof preferably fall within the above-mentioned ranges.

[0042] The binder resin composition for toner of the present invention may further contain other resins such as the above-mentioned composite resin (A) and the below-mentioned amorphous polyester resin (B) in addition to the condensate (AP) within a range that does not impair the effects of the present invention. From the viewpoint of increasing the positive chargeability and improving the image density and fine line reproducibility, the content of the condensate (AP) in the binder resin composition is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, and is preferably 55% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less.

[0043] (Amorphous polyester resin (B)) The binder resin composition for toner of the present invention may further contain an amorphous polyester resin (B) (hereinafter, simply referred to as "resin (B)") from the viewpoint of improving low-temperature fixing property and hot offset resistance.

[0044] The resin (B) is preferably, for example, an amorphous polyester resin containing a polycondensate of an alcohol component and a carboxylic acid component. Examples of the polyester resin include polyester resin and modified polyester resin. Examples of the modified polyester resin include urethane modified polyester resin and epoxy modified polyester resin. Among these, amorphous polyester resin, which is a polycondensation product of an alcohol component and a carboxylic acid component, is preferable.

[0045] The alcohol component may be an alkylene oxide adduct of an aromatic diol, a linear or branched aliphatic diol, an alicyclic diol, or a trihydric or higher polyhydric alcohol, similar to the alcohol component of the polyester resin segment of the composite resin (A) described above, and among these, from the viewpoint of obtaining a toner having excellent low-temperature fixing properties, an alkylene oxide adduct of an aromatic diol is preferred, an alkylene oxide adduct of bisphenol A is more preferred, and a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] or an ethylene oxide adduct of bisphenol A is even more preferred. These may be used alone or in combination of two or more.

[0046] Examples of the carboxylic acid component include the same dicarboxylic acids and trivalent or higher polyvalent carboxylic acids as the carboxylic acid component of the polyester resin segment of the composite resin (A) described above. Examples of dicarboxylic acids include aromatic dicarboxylic acids, linear or branched aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Among these, at least one selected from aromatic dicarboxylic acids and linear or branched aliphatic dicarboxylic acids is preferred. The amount of aromatic dicarboxylic acid in the carboxylic acid component is preferably 40 mol% or more, more preferably 50 mol% or more, even more preferably 60 mol% or more, and is preferably 95 mol% or less, more preferably 85 mol% or less, even more preferably 75 mol% or less.

[0047] The amount of linear or branched aliphatic dicarboxylic acid in the carboxylic acid component is preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, and is preferably 60 mol% or less, more preferably 30 mol% or less, even more preferably 20 mol% or less.

[0048] When a trivalent or higher polycarboxylic acid is contained, the amount of the trivalent or higher polycarboxylic acid in the carboxylic acid component is preferably 3 mol% or more, more preferably 5 mol% or more, even more preferably 8 mol% or more, and is preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 20 mol% or less. These carboxylic acid components may be used alone or in combination of two or more.

[0049] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0050] The resin (B) may be produced, for example, by the step A of polycondensing an alcohol component and a carboxylic acid component. Step A is the same as step A described in the production method of composite resin (A), and the preferred ranges are also the same.

[0051] [Physical properties of amorphous polyester resin (B)] The glass transition temperature of resin (B) is preferably 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher, and from the viewpoint of further improving low-temperature fixability, is preferably 90° C. or lower, more preferably 80° C. or lower, and even more preferably 70° C. or lower. The softening point of resin (B) is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 100°C or higher, and from the viewpoint of further improving low-temperature fixability, it is preferably 160°C or lower, more preferably 150°C or lower, and even more preferably 145°C or lower.

[0052] The acid value of the resin (B) is preferably 1 mgKOH / g or more, more preferably 2 mgKOH / g or more, even more preferably 3 mgKOH / g or more, and is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, even more preferably 10 mgKOH / g or less. The hydroxyl value of resin (B) is preferably 20 mgKOH / g or more, more preferably 25 mgKOH / g or more, even more preferably 30 mgKOH / g or more, and is preferably 50 mgKOH / g or less, more preferably 45 mgKOH / g or less, even more preferably 40 mgKOH / g or less.

[0053] The glass transition temperature, softening point, acid value, and hydroxyl value of the resin (B) can be appropriately adjusted by the types and amounts of raw material monomers used, as well as production conditions such as reaction temperature, reaction time, and cooling rate, and these values ​​can be determined by the methods described in the examples. When two or more resins (B) are used in combination, the softening point, glass transition temperature and acid value of the mixture thereof preferably fall within the above-mentioned ranges.

[0054] The content of the resin (B) in the binder resin composition is preferably 35% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, and preferably 65% ​​by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less.

[0055] (Crystalline polyester resin (C)) From the viewpoint of improving low-temperature fixability, the toner of the present invention preferably contains a crystalline polyester resin (C) (hereinafter, also simply referred to as "resin (C)").

[0056] The resin (C) is, for example, a crystalline polyester resin which is a polycondensation product of an alcohol component and a carboxylic acid component. The alcohol component is preferably an α,ω-aliphatic diol. The α,ω-aliphatic diol has preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, and preferably 16 or less, more preferably 14 or less, even more preferably 12 or less. Examples of α,ω-aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, and 1,14-tetradecanediol. Among these, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred, and 1,6-hexanediol is more preferred.

[0057] The amount of α,ω-aliphatic diol in the alcohol component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, even more preferably 100 mol%.

[0058] The alcohol component may contain other alcohol components different from the α,ω-aliphatic diol. Examples of the other alcohol components include aliphatic diols other than α,ω-aliphatic diols, such as 1,2-propanediol and neopentyl glycol; aromatic diols, such as alkylene oxide adducts of bisphenol A; and trihydric or higher alcohols, such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination.

[0059] The carboxylic acid component is preferably an aliphatic dicarboxylic acid, more preferably a straight-chain aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid preferably has 4 or more carbon atoms and preferably has 14 or less, more preferably 12 or less carbon atoms. Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among these, fumaric acid, sebacic acid, and tetradecanedioic acid are preferred, and fumaric acid is more preferred. These carboxylic acid components may be used alone or in combination.

[0060] The amount of aliphatic dicarboxylic acid in the carboxylic acid component is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and is 100 mol% or less, even more preferably 100 mol%.

[0061] The carboxylic acid component may contain other carboxylic acid components different from the aliphatic dicarboxylic acid. Examples of other carboxylic acid components include aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid, and polyvalent carboxylic acids having three or more carboxylic acids. These carboxylic acid components may be used alone or in combination.

[0062] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component [COOH groups / OH groups] is preferably 0.7 or more, more preferably 0.8 or more, and is preferably 1.3 or less, more preferably 1.2 or less.

[0063] The resin (C) may be produced, for example, by the step A of polycondensing an alcohol component and a carboxylic acid component. Step A is the same as step A described in the production method of composite resin (A), and the preferred ranges are also the same except for the temperature of the polycondensation reaction. The temperature of the polycondensation reaction in the production method of the resin (C) is preferably 110° C. or higher, more preferably 120° C. or higher, and even more preferably 130° C. or higher, and is preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower. The polycondensation may be carried out in an inert gas atmosphere.

[0064] [Physical properties of crystalline polyester resin (C)] From the viewpoint of the storage stability of the toner, the softening point of the resin (C) is preferably 60° C. or higher, more preferably 70° C. or higher, and even more preferably 80° C. or higher, and from the viewpoint of further improving the low-temperature fixing ability, it is preferably 150° C. or lower, more preferably 140° C. or lower, and even more preferably 130° C. or lower. From the viewpoint of the storage stability of the toner, the melting point of the resin (C) is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher, and from the viewpoint of further improving the low-temperature fixing property, it is preferably 150°C or lower, more preferably 140°C or lower, and even more preferably 130°C or lower.

[0065] The acid value of the resin (C) is preferably 1 mgKOH / g or more, more preferably 2 mgKOH / g or more, even more preferably 3 mgKOH / g or more, and preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, even more preferably 10 mgKOH / g or less.

[0066] The softening point, melting point and acid value of the resin (C) can be appropriately adjusted by the type and amount of the raw material monomer, as well as production conditions such as reaction temperature, reaction time, cooling rate, etc., and are determined by the method described in the Examples below. When two or more types of resin (C) are used in combination, it is preferable that the softening point, melting point and acid value obtained as a mixture thereof are each within the above-mentioned ranges.

[0067] The content of the resin (C) in the binder resin composition is preferably 3 mass % or more, more preferably 5 mass % or more, even more preferably 8 mass % or more, and preferably 20 mass % or less, more preferably 18 mass % or less, even more preferably 15 mass % or less.

[0068] [Electrophotographic toner] The toner for electrophotography of the present invention (hereinafter also referred to as "the toner of the present invention") contains the binder resin composition for toner, and preferably contains a colorant and the binder resin composition for toner. The toner of the present invention contains, for example, toner base particles and an external additive. The toner base particles contain the binder resin composition for toner, and preferably contain a colorant and the binder resin composition for toner. The toner base particles may contain, for example, a colorant derivative, a charge control agent, a release agent such as wax, and other additives. From the viewpoint of increasing the positive chargeability of the toner and improving the image density and fine line reproducibility, the content of the binder resin composition for a toner in the toner base particles is preferably 60% by mass or more, more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, and is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less.

[0069] [Coloring Agent] In the present invention, the toner base particles preferably contain a colorant. As the colorant, any of the dyes, pigments, etc. used as toner colorants can be used. Examples of colorants include carbon black, phthalocyanine blue (e.g., pigment blue 15:3), permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, and disazo yellow. The toner may be either a black toner or a color toner other than black. The content of the colorant in the toner base particles is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0070] [Release Agent] In the present invention, the toner base particles preferably contain a release agent. Examples of the release agent include polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, hydrocarbon waxes such as microcrystalline wax, paraffin wax, Fischer-Tropsch wax, and Sasol wax, or oxides thereof, ester waxes such as carnauba wax, montan wax, or deacidified waxes thereof, and fatty acid ester wax, fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.

[0071] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, and preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 100° C. or lower. The content of the release agent in the toner base particles is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, even more preferably 3% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less.

[0072] [Charge control agent] The toner of the present invention may contain a charge control agent. The charge control agent may be either a positively chargeable charge control agent or a negatively chargeable charge control agent. Among these, a positively chargeable charge control agent is preferred. Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron (registered trademark) N-01", "Bontron (registered trademark) N-04", "Bontron (registered trademark) N-07", "Bontron (registered trademark) N-09", and "Bontron (registered trademark) N-11" (all manufactured by Orient Chemical Industry Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain, quaternary ammonium salt compounds such as "Bontron (registered trademark) P-51" (manufactured by Orient Chemical Industry Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Chemical Industry Co., Ltd.); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Chemical Industry Co., Ltd.).

[0073] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast (registered trademark) Black 3804", "Bontron (registered trademark) S-31", "Bontron (registered trademark) S-32", "Bontron (registered trademark) S-34", "Bontron (registered trademark) S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizen Spiron Black TRH", "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.), etc.; metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron (registered trademark) E-81", "Bontron (registered trademark) E-84", "Bontron (registered trademark) E-88", "Bontron (registered trademark) E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.), etc.; copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE PX VP434" (Clariant), nitroimidazole derivatives, etc.; organometallic compounds, etc. These charge control agents may be used alone or in combination of two or more kinds.

[0074] The content of the charge control agent is preferably 1 part by mass or more, more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, and is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 18 parts by mass or less, relative to 100 parts by mass of the total amount of the binder resin components of the toner.

[0075] [Other additives] The toner base particles may further contain, as other additives, additives such as magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, an antiaging agent, and a cleaning property improver, as appropriate.

[0076] In the toner of the present invention, the content of the toner base particles is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and is 100% by mass or less, preferably 99% by mass or less.

[0077] The volume median particle size of the toner base particles (D 50) is preferably 2 μm or more, more preferably 3 μm or more, even more preferably 4 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less. 50 ) means the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size.

[0078] [External additives] The toner of the present invention may further contain an external additive in order to improve fluidity. Examples of the external additive include inorganic material particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic particles such as resin particles such as melamine resin particles and polytetrafluoroethylene resin particles. These may be used alone or in combination. Among these external additives, silica is preferred, and hydrophobic silica treated with a hydrophobic treatment agent is more preferred.

[0079] Examples of hydrophobic treatment agents include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), silicone oil, octyltriethoxysilane (OTES), and methyltriethoxysilane. Among these, hexamethyldisilazane is preferred.

[0080] When the toner base particles are surface-treated using an external additive, the content of the external additive in the toner of the present invention is, from the viewpoint of the chargeability and flowability of the toner, preferably 0.5 parts by mass or more, more preferably 0.8 parts by mass or more, even more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 4 parts by mass or less, relative to 100 parts by mass of the toner base particles.

[0081] The toner of the present invention may be a toner obtained by any of the known methods such as a melt kneading method, an emulsion phase inversion method, a suspension polymerization method, an emulsion aggregation method, etc., but from the viewpoints of productivity and dispersibility of the colorant, a pulverized toner obtained by a melt kneading method is preferred. In the melt-kneading method, the binder resin composition for toner, a colorant, and, if necessary, a property improver such as a release agent are uniformly dispersed, and then the mixture is melt-kneaded, cooled, pulverized, and classified by a known method to obtain a volume median particle size (D 50 ) A toner having a particle size of 2 μm or more and 20 μm or less can be obtained.

[0082] The toner of the present invention is used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing, etc. The toner can be used as a one-component developer, or mixed with a carrier to form a two-component developer. EXAMPLES

[0083] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like were measured by the following methods.

[0084] [measurement] [Resin softening point, crystallinity index, melting point, glass transition temperature] (1) Softening point Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point.

[0085] (2) Crystallinity index Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of sample was weighed into an aluminum pan and cooled to 0°C at a rate of 10°C / min. The sample was then left to stand for 1 minute, after which it was heated to 180°C at a rate of 10°C / min and the calorific value was measured. The temperature of the peak with the largest peak area among the observed endothermic peaks was taken as the endothermic maximum peak temperature (1), and the crystallinity index was calculated by (softening point (°C)) / (endothermic maximum peak temperature (1) (°C)).

[0086] (3) Melting point and glass transition temperature Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan Co., Ltd.), 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled from that temperature to 0°C at a rate of 10°C / min. The sample was then heated at a rate of 10°C / min, and the calorific value was measured. Among the endothermic peaks observed, the temperature of the peak with the largest peak area was taken as the maximum endothermic peak temperature (2). In the case of a crystalline resin, this peak temperature was taken as the melting point. In the case of an amorphous resin, when a peak was observed, the temperature of the peak was taken as the glass transition temperature. When no peak was observed but a step was observed, the temperature at the intersection of the tangent showing the maximum slope of the curve at the step and an extension of the baseline on the low temperature side of the step was taken as the glass transition temperature.

[0087] [Acid value and hydroxyl value of resin] Measurements were performed in accordance with JIS K0070:1992, except that the measurement solvent was chloroform.

[0088] [Amine value of resin] 1.0 to 1.5 g of sample was accurately measured and placed in a 150 mL beaker, and about 70 mL of ethyl alcohol was added to dissolve the sample solution. 2 to 3 drops of phenolphthalein indicator solution were added to the sample solution, and 10 mass % sodium hydroxide solution was added to make it weakly alkaline. Using a potentiometric titrator, the solution was titrated with 0.2 mol / L alcoholic hydrochloric acid standard solution until the first and second equivalence points were passed. The amine value was then calculated using the following formula 1.

[0089]

number

[0090] In formula 1, A, B, and f are as follows. A: The amount (mL) of 0.2 mol / L alcoholic hydrochloric acid standard solution required for titration up to the first equivalence point B: Amount (mL) of 0.2 mol / L alcoholic hydrochloric acid standard solution required for titration up to the second equivalence point f: Factor of 0.2 mol / L alcoholic hydrochloric acid standard solution

[0091] [Dielectric constant] 3 g of the resin sample was weighed and melt-pressed in a hot press at 75°C and 20 MPa to produce a disk-shaped resin pellet. The dielectric constant was then measured using an Agilent 16451B dielectric measurement electrode (manufactured by Agilent Technologies).

[0092] [Volume median particle diameter of toner base particles D 50 〕 Volume median particle size D of toner base particles 50 was measured as follows: Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "EMULGEN (registered trademark) 109P" (manufactured by Kao Corporation, HLB: 13.6) was dissolved in the electrolyte to obtain a dispersion liquid with a concentration of 5% by mass. Dispersion conditions: 10 mg of a toner measurement sample was added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Thereafter, 25 mL of electrolyte was added, and the mixture was further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size D is calculated from the particle size distribution. 50 asked for.

[0093] [Number average molecular weight (Mn) of polyalkyleneimine (P)] The molecular weight distribution was measured by the gel permeation chromatography (GPC) method described below to determine the number average molecular weight. (1) Preparation of sample solution Polyalkyleneimine (P) was dissolved in a solution of 0.15 mol / L of Na2SO4 dissolved in 1% by mass aqueous acetic acid so as to give a concentration of 0.2 g / 100 mL. Next, this solution was filtered using a fluororesin filter "FP-200" (manufactured by Sumitomo Electric Industries, Ltd.) with a pore size of 0.2 μm to remove insoluble components, and a sample solution was obtained. (2) Molecular weight measurement The following measuring equipment and analytical column were used, and a solution of 0.15 mol / L Na2SO4 dissolved in 1% by weight aqueous acetic acid was passed through the column at a flow rate of 1 mL per minute, and the column was stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution was injected into the column for measurement. The molecular weight of the sample was calculated based on a calibration curve that had been prepared in advance. The calibration curve used here included several types of standard pullulan "P-5" (5.9 x 10 3 ), "P-50" (4.73 x 10 4 ), "P-200" (2.12 x 10 5 ), "P-200" (2.12 x 10 5 ), "P-800" (7.08 x 10 5 ) (both manufactured by Showa Denko K.K.) were used as standard samples. Measuring device: "HLC-8320GPC" (manufactured by Tosoh Corporation) Analytical column: α+α-M+α-M (Tosoh Corporation)

[0094] [Resin manufacturing] Production example A1 (condensate AP-1) 3536g of propylene oxide (2.2) adduct of bisphenol A and 1407g of ethylene oxide (2.2) adduct of bisphenol A were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 100°C, after which 1880g of terephthalic acid was added and the temperature was raised to 160°C. While maintaining the temperature at 160°C, a mixture of 1592g of styrene, 42g of acrylic acid and 64g of dibutyl peroxide was added dropwise over 1 hour, reacted for 60 minutes, and then heated to 200°C. The pressure in the flask was further reduced and the reaction was carried out at 8kPa for 1 hour under reduced pressure. Thereafter, 35g of di(2-ethylhexanoate)tin(II) and 3.5g of gallic acid were added, the temperature was raised to 235°C, and the reaction was carried out at 235°C for 8 hours. Thereafter, the mixture was cooled to 150°C, and 193 g of fumaric acid, 3.5 g of 4-tert-butylcatechol, and 169 g of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-006, molecular weight 600) were added, and the mixture was heated to 160°C and reacted for 1 hour. Thereafter, the mixture was heated to 200°C at a rate of 10°C / h, the pressure in the flask was reduced, and the reaction was carried out at reduced pressure of 8 kPa for 1 hour to obtain a condensate AP-1.

[0095] Production example A2 (condensate AP-2) 3535g of propylene oxide (2.2) adduct of bisphenol A and 1407g of ethylene oxide (2.2) adduct of bisphenol A were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 100°C, after which 1880g of terephthalic acid was added and the temperature was raised to 160°C. While maintaining the temperature at 160°C, a mixture of 1337g of styrene, 255g of 2-ethylhexyl acrylate, 42g of acrylic acid, and 64g of dibutyl peroxide was added dropwise over 1 hour, reacted for 60 minutes, and then heated to 200°C. The pressure in the flask was further reduced, and the reaction was carried out under reduced pressure at 8kPa for 1 hour. Thereafter, 35g of di(2-ethylhexanoate)tin (II) and 3.5g of gallic acid were added, the temperature was raised to 235°C, and the reaction was carried out at 235°C for 8 hours. Thereafter, the mixture was cooled to 150°C, and 193 g of fumaric acid, 3.5 g of 4-tert-butylcatechol, and 169 g of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-006, molecular weight 600) were added, and the mixture was heated to 160°C and reacted for 1 hour. Thereafter, the mixture was heated to 200°C at a rate of 10°C / h, and the pressure in the flask was reduced, and the reaction was carried out at reduced pressure of 8 kPa for 1 hour, to obtain a condensate AP-2.

[0096] Production example A3 (condensate AP-3) A condensation product AP-3 was obtained in the same manner as in Production Example A2, except that the amounts of the raw materials used in Production Example A2 were changed as shown in Table 1.

[0097] Manufacturing example A4 (resin D-1) 4445g of propylene oxide (2.2) adduct of bisphenol A and 1769g of ethylene oxide (2.2) adduct of bisphenol A were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the mixture was heated to 100°C, after which 2364g of terephthalic acid was added, the mixture was heated to 160°C, 45g of di(2-ethylhexanoate)tin(II) and 4.5g of gallic acid were added, the mixture was heated to 235°C, and the mixture was reacted for 8 hours at 235°C. Thereafter, the mixture was cooled to 150°C, and 242g of fumaric acid, 4.5g of 4-tert-butylcatechol, and 169g of polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., trade name: SP-006, molecular weight 600) were added, and the mixture was heated to 160°C and reacted for 1 hour. Thereafter, the temperature was increased to 200° C. at a rate of 10° C. / h, the pressure inside the flask was reduced, and the reaction was carried out under reduced pressure at 8 kPa for 1 hour to obtain Resin D-1 as a polyethyleneimine-modified polyester resin.

[0098] Manufacturing example A5 (resin A-1) 3670g of propylene oxide (2.2) adduct of bisphenol A and 1436g of ethylene oxide (2.2) adduct of bisphenol A were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the mixture was heated to 100°C, after which 1919g of terephthalic acid was added and the mixture was heated to 160°C. While maintaining the temperature at 160°C, a mixture of 1364g of styrene, 260g of 2-ethylhexyl acrylate, 42g of acrylic acid, and 65g of dibutyl peroxide was added dropwise over 1 hour, reacted for 60 minutes, and then heated to 200°C. The pressure in the flask was further reduced, and the reaction was carried out at reduced pressure for 1 hour at 8kPa. Then, 35g of di(2-ethylhexanoate)tin(II) and 3.5g of gallic acid were added, the mixture was heated to 235°C, and the mixture was reacted at 235°C for 8 hours. After that, it was cooled to 150°C, 196g of fumaric acid and 3.5g of 4-tert-butylcatechol were added, and the temperature was raised to 160°C and reacted for 1 hour. After that, the temperature was raised to 200°C at 10°C / h, the pressure in the flask was reduced, and the reaction was carried out at reduced pressure of 8kPa for 1 hour to obtain Resin A-1 as Composite Resin (A).

[0099] [Table 1] *1: BPA-PO means a polyoxypropylene (2,2) adduct of bisphenol A. BPA-EO means a polyoxyethylene (2,2) adduct of bisphenol A. *2: This refers to the molar parts of each monomer constituting the raw material monomer and the bireactive monomer when the alcohol component of the raw material monomer of the polyester resin segment is taken as 100 molar parts. *3: This refers to the content (mass%) of each monomer that constitutes the raw material monomer in the total amount of the vinyl resin segment. *4: The amount of polymerization initiator added (parts by mass) when the total amount of the vinyl resin segment is 100 parts by mass. *5: This refers to the polyalkyleneimine content (mass%) when the total amount of the condensate (resin) is 100 parts by mass. *6: This refers to the content (mass%) of the vinyl resin segment relative to the total amount of the polyester resin segment and the vinyl resin segment. *7: PEI600 means polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name "SP-006", molecular weight 600).

[0100] Production example B (resin B-1) 4477g of propylene oxide (2.2) adduct of bisphenol A and 1782g of ethylene oxide (2.2) adduct of bisphenol A were placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 160°C, after which 1699g of terephthalic acid, 481g of trimellitic acid, 561g of dodecenylsuccinic anhydride and 45g of tin (II) di(2-ethylhexanoate) were added, the temperature was raised to 235°C and the reaction was carried out at 235°C for 7 hours. Thereafter, the pressure in the flask was reduced, and the reaction was carried out at reduced pressure of 8kPa for 1 hour to obtain resin B-1 as an amorphous polyester resin.

[0101] [Table 2]

[0102] Production example C (resin C-1) 4539g of 1,6-hexanediol was placed in a 10-liter four-neck flask equipped with a dehydration tube equipped with a nitrogen inlet tube, a stirrer, and a thermocouple, and the temperature was raised to 100°C. After heating, 4462g of fumaric acid, 18g of tin(II) di(2-ethylhexanoate) and 4.5g of 4-tert-butylcatechol were added and the temperature was raised to 140°C. After reacting for one hour, the temperature was raised to 150°C and reacted for one hour. The temperature was raised to 200°C at 10°C / h, and the reaction was carried out at 8.0kPa for 3 hours to obtain Resin C-1 as a crystalline polyester resin.

[0103] [Table 3]

[0104] [Toner manufacturing] Examples 1 to 3 and Comparative Examples 1 to 2 40 parts by mass of condensates AP-1 to 3, resin D-1, or resin A-1 shown in Table 4, 50 parts by mass of resin B-1 as an amorphous polyester resin, 10 parts by mass of resin C-1 as a crystalline polyester resin, 6 parts by mass of colorant "ECB-301" (manufactured by Dainichi Seikagaku Kogyo Co., Ltd.), 7 parts by mass of release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd.), and 15 parts by mass of positively charged charge control agent "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.) were stirred for 3 minutes at a rotation speed of 1500 r / min (circumferential speed 21.6 m / sec) using a Henschel mixer, and then the mixture was mixed with a co-rotating twin-screw extruder (manufactured by Ikegai Co., Ltd., product name: PCM-30, shaft diameter 2.9 cm, shaft cross-sectional area 7.06 cm). 2 The roll rotation speed was 200 r / min (circumferential speed 0.30 m / sec), the barrel temperature was set to 1000°C, and the feed rate of the mixture was 10 kg / h (mixture feed rate per unit cross-sectional area of ​​the shaft: 1.42 kg / h cm 2 ) was.

[0105] The kneaded product thus obtained was rolled and cooled with a cooling roll, and then coarsely pulverized to about 1 mm using a hammer mill. The coarsely pulverized product thus obtained was finely pulverized and classified using an air jet mill (manufactured by Nippon Pneumatic Co., Ltd., product name: IDS) to obtain a volume median particle size (D 50 ) toner base particles of 7.0 μm were obtained. 100 parts by mass of the obtained toner base particles and 0.5 parts by mass of hydrophobic silica "TG-820F" (manufactured by Cabot Specialty Chemicals, Inc., number average particle size: 8 nm) as external additives, 2.0 parts by mass of hydrophobic silica "NA-50Y" (manufactured by Nippon Aerosil Co., Ltd., number average particle size: 30 nm), and 0.4 parts by mass of polytetrafluoroethylene fine particles "KTL-500F" (manufactured by Kitamura Co., Ltd., number average particle size: 500 nm) were mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at 2100 r / min (circumferential speed: 29 m / sec) for 3 minutes to obtain a toner.

[0106] [evaluation] [Image Density] The toner obtained above was mounted on a non-magnetic one-component developing device (manufactured by Brother Industries, Ltd., product name: HL-2040), and a solid image was printed in an environment of 25°C and 50% humidity. The image density of the obtained image was then measured at four points on each printed image using a colorimeter (manufactured by GretagMacbeth, product name: GretagMacbeth Spectroeye), and the average value was calculated as the image density, and the image density was evaluated. The higher the image density, the better the image quality. The results are shown in Table 4.

[0107] [Fine line reproducibility] The toner obtained above was mounted on a non-magnetic single-component developing device (Brother Industries, Ltd., product name: HL-2040), and a 1 dot / 3 space / horizontal line pattern was printed in an environment of 25°C and relative humidity of 50%. The reproducibility of the 1 dot line was confirmed with a digital microscope (Olympus Corporation, product name: DSX510, using a 50x lens, observation conditions: 693x), and the fine line reproducibility was evaluated according to the following criteria A to D. Image quality is excellent if it is criterion B or higher. The results are shown in Table 4. A: There are 5 or fewer breaks in a 1-dot line (1 line / cm). B: There are 6 to 12 discontinuities in a 1-dot line (1 line / cm). C: There are 13 to 20 discontinuities in a 1-dot line (1 line / cm). D: There are 21 or more discontinuities in a 1-dot line (1 line / cm).

[0108] [Table 4]

[0109] From the results of the Examples and Comparative Examples, it was found that the toner using the binder resin composition for toner of the present invention is excellent in image density and fine line reproducibility, and improves the image quality of printed matter. This is believed to be due to the fact that the dielectric constant of the condensate (AP) contained in the binder resin composition for toner of the present invention is improved, thereby increasing the positive chargeability.

Claims

1. A composite resin (A) including a polyester resin segment which is a polycondensation product of an alcohol component and a carboxylic acid component, and a vinyl resin segment which is an addition polymerization product of a raw material monomer including a styrene compound; A binder resin composition for toner, comprising a condensate (AP) of a polyalkyleneimine (P).

2. The binder resin composition for toner according to claim 1 , wherein the content of the styrene-based compound in the raw material monomers of the vinyl-based resin segment is 70% by mass or more.

3. 3. The binder resin composition for toner according to claim 1, wherein the content of the vinyl resin segment in the composite resin (A) is from 5% by mass to 30% by mass.

4. 4. The binder resin composition for toner according to claim 1, wherein the condensate (AP) contains 0.5% by mass or more and 5% by mass or less of a constitutional unit derived from the polyalkyleneimine (P).

5. 5. The binder resin composition for toner according to claim 1, wherein the amine value of the condensate (AP) is from 5 mgKOH / g to 80 mgKOH / g.

6. 6. An electrophotographic toner comprising the binder resin composition for toners according to claim 1.

Citation Information

Patent Citations

  • Dry toner

    JP1986014644A

  • Positively-charged toner for electrostatic charge image development

    JP2019035959A

  • Binder resin composition for toner

    JP2020020866A

  • Binder resin composition for toner

    JP2020024360A

  • Toner for electrostatic charge image development

    JP2021043418A